Experimental and numerical studies of the mechanical properties of nitrile-butadiene rubber exposed to gamma radiation. (July 2023) - Chayoukhi, S.; Abid, M.; Gassoumi, B.; Mejri, A.; Boukhachem, A.; Amlouk, M.
Abstract: In this study, the effects of gamma radiation on the mechanical properties of nitrile-butadiene rubber (NBR) samples are examined employing experimental tensile and hardness tests. The NBR is exposed to different doses of gamma radiation (0, 30, 45, 60, 75 and 90 kGy) at room temperature. The obtained results indicate an improvement in the elastic behavior of NBR specimens and a diminution of their plastic behavior with the increase in the absorbed dose. The morphology properties of pristine and irradiated NBR were evaluated by scanning electron microscopy (SEM). A numerical simulation is performed by using five hyperelastic models included in Abaqus: Mooney Rivlin model, Ogden model, Yeoh model, Arruda-Boyce model and Neo-Hookean model. The input data utilized in the conducted simulation are taken from experimental tensile results. The validation of the five hyperelastic models shows that they are stable in tension for both virgin and irradiated samples. The stress-strain curves of both virgin and gamma-irradiated NBR rubber samples are presented and the coefficients of the hyperelastic strain energy function are calculated for all models. The comparison of the simulated results with the experimental measurements demonstrates that the Ogden model provides the best fitting curvature of the stress-strain curves for virgin and irradiated samples. It gives the lowest mean square error. The latter decreases with the rise of the absorbed gamma dose and it is in all cases less than 0.51%. Thus, this model is appropriately applied to better simulate the mechanical behavior of the unirradiated and irradiated NBR. Experimental and numerical results are promising for predicting the behavior of NBR rubber exposed to gamma radiation. Highlights: NBR material was irradiated with gamma rays ranging from 0 to 90 kGy. Gamma irradiation improved stiffness, hardness and cross-linking density. Gamma irradiation reduces plastic properties. Numerical simulation was performed to predict the hyperelastic behavior of NBR.